Dampak Pandemi Covid-19 Terhadap Dinamika Ekspor ASEAN 5: Pendekatan Panel Kointegrasi - Hanafi, Ridwan Umar (Pusat Pendidikan dan Pelatihan Aparatur Perdagangan, 2021)
This study examine the effect of COVID-19 pandemic on ASEAN5 export performance. The study begins with an exploration of ASEAN5 export data, before and after pandemic. Panel cointegration model (FMOLS and DOLS) is applied to determine the long-term relationship between exports and pandemic. During pandemic, energy exports performance (such as coal, natural gas, and oil) decreased. In general, machineries (HS 84) also experienced a decline in export performance. On the other hand, exports of palm oil and gold were able to grow positively. Exports of the electrical equipment (HS 85) were also able to grow positively for most countries. FMOLS and DOLS models showed a long-term relationship between exports and the pandemic. Furthermore, pandemic and real exchange rate have a negative relationship with exports while economic liquidity (M2) has a positive effect on exports.